Efektivitas metode ceramah dan small group discussion tentang kesehatan reproduksi terhadap tingkat pengetahuan dan sikap remaja SMA muhammadiyah sokaraja - Kristia Rahmawati; Devita Elsanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Reproductive health education is basically an attempt to provide knowledge. Possible reproductive health problems experienced by adolescents include unwanted pregnancy (KTD), abortion, sexually transmitted diseases (STDs), sexual violence, and the problem of limited access to information and health services. Objective: The aim of this research was to determine the effectiveness of the lecture method and small group discussion about reproductive health toward the level of knowledge and attitudes of adolescents. Research Methods: This research was a quantitative study using Quasi-Experimental Design with the Pretest-Posttest Design approach. The sampling technique used in this research was total sampling with a sample size of 62 respondents which was divided into two groups. There were 31 participants who used the lecture method and the other 31 participants used the small group discussion method. Results: The results showed that reproductive health education towards the level of knowledge and attitudes of adolescents with the lecture method and small group discussion were each effective toward the level of knowledge and attitude. The difference in the average pretest-posttest lecture method and small group discussion on the level of knowledge was 4.22 greater small group discussion methods which showed that the small group discussion method was more effective in increasing the level of knowledge of respondents. On the other hand, the difference between the average pretest-posttest lecture method and small group discussion on attitudes was 5.1 larger small group discussion methods which showed that the small group discussion method was more effective in increasing the level of knowledge of respondents. Conclusion: The results show that small group discussions are more effective in increasing the level of knowledge and attitudes of respondents towards adolescent reproductive health. Keywords: Knowledge Level, Attitudes, Adolescent Reproductive Health, Lectures, Small Group Discussion.